Expectations, learning and monetary policy: an overview of recent research - George W. Evans; Seppo Honkapohja (Bank of Finland, 2007)
Expectations about the future are central for determination of current macroeconomic outcomes and the formulation of monetary policy. Recent literature has explored ways for supplementing the benchmark of rational expectations with explicit models of expectations formation that rely on econometric learning. Some apparently natural policy rules turn out to imply expectational instability of private agents' learning. We use the standard New Keynesian model to illustrate this problem and survey the key results for interest-rate rules that deliver both uniqueness and stability of equilibrium under econometric learning. We then consider some practical concerns such as measurement errors in private expectations, observability of variables and learning of structural parameters required for policy. We also discuss some recent applications, including policy design under perpetual learning, estimated models with learning, recurrent hyperinflation, and macroeconomic policy to combat liquidity traps and deflation.
URN:NBN:fi:bof-20140807289
Keywords: E52; E31; D84; 330; imperfect knowledge; learning; interest-rate setting; fluctuations; stability; determinacy